Analysis of Society Perspective about Vintage Fashion Using Deconstruction Approach - Assayyidah Bil Ichromatil Ilmi (JURNAL RUPA, 2021)
Nowadays, society perspective about vintage fashion as old-fashioned can be changed. This study aims to discuss the alteration perspective of society about vintage fashion. This discussion is conducted to see the other side of vintage fashion. This research is different from other fashion studies because it wants to show how to view the value of a fashion not in general way, especially using deconstruction approach. This study used qualitative methods in the form of interviews to get the data. The interviewees of this research were four young women who like to follow fashion development through social media. Their opinions are used as society representatives about vintage fashion. It will be connected with the theory of deconstruction like 'Differance.' In this case, people's perspective on vintage fashion changes due to the influence of influencers from various social media so that vintage fashion can be juxtaposed with modern style today. Therefore, vintage can get an identity as nowadays's clothes.